Assessing climate change vulnerability in riparian communities: A case study from the Teesta-Jamuna river basin, Bangladesh - Most. Mitu Akter; N M Refat Nasher (National Geographical Journal of India, 2024)
Millions of low-income people have been living in physically vulnerable char and riverbank areas through the decades under adverse environmental conditions. The inhabitants of charland and the riverbanks are frequently impacted by the dangers of climate change. This is because their livelihoods heavily rely on agriculture. The purpose of this research was to evaluate potential exposure levels between char (Chilmari Upazila; Gaibandha) and riverbank (Sundorganj upazila; Kurigram) households using the Livelihood vulnerability index (LVI) and the Livelihood vulnerability index-Intergovernmental Panel on climate change (LVI-IPCC). The LVI was computed by amalgamating the three components, namely exposure, sensitivity, and adaptive capability, utilizing the LVI and LVI-IPCC. A comprehensive survey was conducted on a total of 272 families, with an equal number of households (136 each) from Chilmari and Sundorganj. The non-probability approach encompassed a wide range of themes, including demographic data, economy, networks of friends, good health, food and water scarcity, variability in the climate, and natural disasters. The LVI scores (Chilmari; 0.533, Sundorganj;0.504) were suggested highly vulnerable to climate change hazards for both areas. The LVI-IPCC results demonstrated that dwellers in Chilmari (score;0.075) were more vulnerable than those in Sundarganj (score;0.028) because of their low productivity, low income, insufficient availability of food and poor provision of healthcare services, and poor social network system. This study suggested that the inhabitants in Char land are more susceptible.than those of riverbank inhabitants in Bangladesh. Easy access to education, better communications to the service area, alternative sources of income, use of high technology in agriculture, and incorporation of the local people during policy design and implementations can effectively improve the ability to adjust and decrease susceptibility to extreme occurrences caused by climate change.